Coexisting with the alien: Evidence for environmental control on trophic interactions between a native (Atherina boyeri) and a non-indigenous fish species (Gambusia holbrooki) in a Mediterranean coastal ecosystem - Andolina, Cristina; Signa, Geraldina; Cilluffo, Giovanna; Iannucci, Simona; Mazzola, Antonio; Vizzini, Salvatrice (Frontiers in Ecology and Evolution, 2022)
Biological invasions are a widespread problem worldwide, as invasive non-indigenous species (NIS) may affect native populations through direct (e.g., predation) or indirect (e.g., competition) trophic interactions, leading to changes in the food web structure. The trophic relationships of the invasive eastern mosquitofish Gambusia holbrooki and the native big-scale sand smelt Atherina boyeri coexisting in three Mediterranean coastal ponds characterised by different trophic status (from oligotrophic to hypereutrophic) were assessed in spring through isotopic niche analysis and Bayesian mixing models. The two fish relied on distinctive trophic pathways in the different ponds, with evidence of minimal interspecific niche overlap indicating site-specific niche divergence mechanisms. In more detail, under hyper- and mesotrophic conditions, the two species occupied different trophic positions but relying on a single trophic pathway, whereas, under oligotrophic conditions, both occupied a similar trophic position but belonging to distinct trophic pathways. Furthermore, the invaders showed the widest niche breadth while the native species showed a niche compression and displacement in the ponds at higher trophic status compared to the oligotrophic pond. We argue that this may be the result of an asymmetric competition arising between the two species because of the higher competitive ability of G. hoolbroki and further shaped by the trophic status through a conjoint effect of prey availability and habitat complexity. While the high trophic plasticity and adaptability of both species to different environmental features and resource availability may have favoured their coexistence through site-specific mechanisms of niche segregation, we provide also empirical evidence of the importance of environmental control in invaded food webs, calling for greater attention to this aspect in future studies.